Epidermotropism of lepra bacilli in a patient with histoid Hansen's disease - Rita V Vora; Abhishek Pilani (Wolters Kluwer Medknow Publications, 2014)
Histoid leprosy is a rare form of multibacillary leprosy with distinct clinical and histopathological features. It is a variant of lepromatous leprosy with a very high bacillary load. It appears in patients as relapse after dapsone monotherapy and resistance or rarely, "de novo." Although leprosy is slowly declining the exact mode of transmission is unclear. At least until recently, the most widely held belief was that the disease was transmitted by contact between cases of leprosy and healthy persons. Transmission by the respiratory route is also gaining ground. There are other possibilities such as transmission through insects, which cannot be completely ruled out. However, the present case report possibly suggests the role of skin as a portal of both exit and entry for the bacillus in histoid leprosy transmission. De novo form of histoid leprosy has numerous solid staining bacteria inside the epidermis. The reports show that these bacilli can be eliminated from the intact epidermis, which indicate an unusual role of the skin in the transmission of leprosy.